Female breast cancer as taboo: cultural factors and awareness amongst patients and their families in the Philippines - Mendoza-Dreisbach, Sharon; Dreisbach, Jeconiah Louis (Penerbit Universiti Kebangsaan Malaysia, 2018)
Statistical information from cancer studies show that the Philippines has the highest incidence rate of breast cancer in Asia. Efforts on creating awareness are being spearheaded by the country’s health department, local governments, and cancer-interest organizations. Despite these, discussions on the issue remain a forbidden topic among many Filipinos, particularly the patients and their families themselves. This study aims to know the central discourses behind the prevailing treatment of Filipinos on female breast cancer as taboo and the correlation to the slow development of awareness on the illness. A quality circle was conducted on three middle-aged women from General Santos City, southern Philippines. All of the respondents were breast cancer survivors. A discourse analysis on the data figured that there are two central and interconnected discourses hindering the awareness and acceptance of breast cancer: (i) fear and denial due to financial instability, and (ii) folk belief. The researchers suggest that instead of coursing breast cancer treatment budget through the Philippine government’s health insurance provider, it should be directly allocated to the country’s health services program. They concluded that beyond creating awareness, it is with the accessibility of treatment that the Filipino people will be liberated from the prevailing central discourses on breast and any type of cancer.